Functional posterior communicating artery of patients with posterior circulation ischemia using phase contrast magnetic resonance angiography - Zhou, Wei (Exp Ther Med, 2019)
Posterior communicating artery (PCoA) in patients with posterior circulation ischemia (PCI) was quantitatively studied using phase contrast magnetic resonance angiography (PC-MRA). Fifty-one cases who received PC-MRA were included in the study, and divided into the research and control groups. The mean flow volume, mean flow velocity, minimum flow volume, maximum flow volume, minimum flow velocity and maximum flow velocity of the basal artery (BA), bilateral vertebral arteries, internal carotid arteries and functional posterior communicating artery (F-PCoA) were recorded, the peak heights of flow volume and flow velocity were calculated, and the typing of F-PCoA was analyzed, followed by statistical analysis. Fifty-two F-PCoAs were detected, and the median values of mean flow volume, mean flow velocity, cross-sectional area and lumen diameter were 20.31 ml/min, 4.01 cm/sec, 0.08 cm(2) and 0.16 cm, respectively. The blood flow curve of F-PCoA showed the sawtooth-like changes, and there could be either unidirectional blood flow or bidirectional blood flow in one cardiac cycle. F-PCoA was divided into the following 3 types: F-PCoA was consistent with anatomical PCoA (A-PCoA), F-PCoA was inconsistent with A-PCoA, and mixed type. In the presence of F-PCoA, both the diameter and cross-sectional area of BA were small, and the maximum flow velocity and peak height of flow volume were reduced, but there was no necessary correlation with the occurrence of PCI. Both flow volume and flow velocity of BA in the research group were reduced, and the forward posterior shunt flow of F-PCoA was increased. Hemodynamic characteristics of F-PCoA can be analyzed via PC-MRA. The forward posterior shunt flow of F-PCoA can provide references for the clinical auxiliary diagnosis.